Application of bicylindroconical machine elements - Kiryushko, V. S.; Volina, Т. М. (НУБіП України, 2023)
Представлені тези доповідей науково-педагогічних працівників, наукових співробітників, аспірантів та студентів НУБіП України, провідних вітчизняних і закордонних вищих навчальних закладів та наукових установ, в яких розглядаються завершені етапи розробок.

The Proceedings presents abstracts of reports of scientific and pedagogical workers, research staff, graduate students and students of the NULES of Ukraine, leading domestic and foreign higher educational institutions and scientific institutions, in which completed stages of development are considered.
Keywords: application of bicylindroconical machine elements; parts is accurate and consistent; motion control systems; assembly process for large machines; lifting loads